Physical and cultural space in pre-industrial Europe : methodological approaches to spatiality - Lamberg, Marko; Hakanen, Marko; Haikari, Janne (Nordic Academic Press, 2011)
Prior to the Industrial Era, the geography of Europe posed problems, but also offered possibilities for its people. This book intends to answer how early modern Europeans - rulers, officials, aristocrats, scholars, priests, and commoners - perceived, utilised and organised the space around them.
Keywords: Historical geography : Europe, Northern; historiallinen maantiede; geopolitiikka; syrjäseudut; rajaseudut; periferiat; välimatkat; tila; rajat; vallanjako; valtarakenteet; historialliset kartat; uuden ajan alku; historia; etäisyys; historisk geografi; geopolitik; perifera regioner; gränstrakter; periferier; distanser; utrymme; gränser; maktfördelning; maktstrukturer; historiska kartor; tidigmodern tid; avstånd; Pohjois-Eurooppa; Ruotsi; Eurooppa; Suomi; Nordeuropa; Sverige; Europa; Finland